Influence of Electronic Money Transfer Services on Performance of Small and Medium Enterprises in Kenya (A CASE OF BUNGOMA COUNTY) - Akwanyi, Marvin; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
According to the 2013 Economic Survey, the SME sector, contributed 18.4% of the country’s Gross Domestic Product (GDP). This shows the importance of SMEs to the Kenyan economy mainly as a source of employment to an ever increasing populationhe use of mobile banking services has continued to grow over time as aapplication of the mobile phones for mobile banking has marked a new frontier in mobile phone technology with an ever increasing number of small and medium enterprises using it in their transactions to enhance their performance. The role of electronic money transfer services has been viewed as a critical element for the performance of small and medium-sized enterprises. Typically, smaller enterprises face higher transactions costs than larger enterprises in obtaining credit Insufficient funding has been made available to finance working capital for the SMEs (Poor efficiency and consumer convenience practices have hampered the ability of smaller and medium enterprises and Entrepreneur ICT Competency such as Information asymmetries associated with lending to small scale borrowers have restricted the flow of finance to smaller and medium enterprises. In spite of these claims however, some studies show a large number of small and medium enterprises fail because of perceived value of m-banking and transaction costs due to poor record keeping and lack of basic business management experience and skills are major contributors to failure of small business. The number of uses to which mobile banking services can be put keeps increasing with time. Small and medium enterprises in Kenya have adopted the use of the mobile payments as a way of transacting their business because of the relative affordability of mobile phones and the mobile banking services they offer. However, it is not clear how mobile banking service use influences the performance of small and medium enterprises. The study sought to determine if its use in Bungoma County, a rural setting, has resulted in improvement on performance of small and medium enterprises. The study will be based on a survey of 3680 small and medium enterprises, from three major sectors of the Kenyan economy, agriculture, service and processing sectors. Small and medium enterprises that will be studied are those that have been in existence for more than 5 years and have experienced business without mobile banking services before 2008, and thereafter with it. The study was built on the theories of diffusion of innovation theory, technology acceptance model and Schumpeter’s theory. The main purpose of this study is to establish influence of mobile banking services on performance of small and medium enterprises in Kenya. The study was guided by the following specific objectives: To find out the influence of mobile transfer services on performance of small and medium enterprises in Kenya; To investigate the influence of internet banking services on performance of small and medium enterprises in Kenya; To examine the influence of access to finance on performance of small and medium enterprises in Kenya; To study the influence of e-commerce on performance of small and medium enterprises in Kenya and to establish the influence of perceived value m-banking on performance of small and medium enterprises in Kenya The study adopted a descriptive survey and a stratified sampling technique method was used and data was collected through the use of questionnaires. The correlation and regression analysis was used to establish the direction and strength of the relationship of the variables at 5% level of significance. The analysis showed that access to finance services had the strongest positive (Pearson correlation coefficient =.852) performance of SMEs. In addition, mobile banking services, internet banking services and e-commerce services were positively correlated to performance